(untitled) (Geographical Journal of Nepal, 2023)
This study identified multiple nature of disasters in Tarai in general and Birgunj - Simara Urban Corridor, one of the hotspots of urbanization in Nepal in particular. Using geospatial technology, secondary sources of information, and stakeholder’s consultations, this study evaluated floods, earthquakes, windstorms, and fire impacts, identified factors contributing to vulnerability, and solutions for increasing resilience. Although rivers have limited floodplains, floods have been increased because of floodplain encroachment, improper drainage, land use changes in upper catchment, and climate change. Although the earthquake could have a high impact, the seismicity is low compared to the national context. During pre- and monsoon seasons, windstorms have a high impact over a limited area and are hard to predict. Fires are not widespread in the settlements but common during hot, dry months due to compact rural settlements, nonresilient house designs, and inadequate safety measures. Besides, lack of adaptation capacity as a result of poor awareness, widespread poverty, and poor disaster response have contributed to a high vulnerability to multihazards. Mitigation actions identified include risk-sensitive land use planning, flood control and hydraulic structure design, efficient urban drainage, waste management, resilient housing, and disaster safety plans. Local communities should be involved in developing early warning systems, disaster preparedness, and response measures.